2/3 - 15(-1/2)^2 + (-1/2)^-2

= 2/3 - 7.5 + 1?

Printable View

- Dec 4th 2005, 11:28 AMx-disturbed-xfractional confusion
2/3 - 15(-1/2)^2 + (-1/2)^-2

= 2/3 - 7.5 + 1? - Dec 4th 2005, 11:45 AMCaptainBlackQuote:

Originally Posted by**x-disturbed-x**

$\displaystyle (-1/2)^{-2}\ =\ (-2).(-2)\ =\ 4$

so now you should be able to complete this yourself.

RonL - Dec 4th 2005, 12:06 PMx-disturbed-xtangents n norms
The equation of a curve is y = 3x^2 - 2x + 1

find the coordinates of the point R on the curve at which the gradient is -14.